APLIKASI PENDEKATAN THEORY OF REASONED ACTION UNTUK MEMPERIKSI MINAT MASUK MENJADI PESERTA MANDIRI BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN (Studi Kasus: Masyarakat Kecamatan Medan Selayang) - Saragih, Nawary (UNIKA Santo Thomas, 2017)
In BPJS Health still happened paradox rights, that is for health protection there is still ambiguity happened at Mitra Hospital which not as expected with that felt by patient, for example for certain sick like cancer for chemo process only long and difficult service for certain reasons as well. This is contrary to expectations by the Minister of Health proposed by Nafsiah Mboi that BPJS Health will endeavor to bear all kinds of diseases. Based on this, the research problem is formulated